Beyond binaries? Spatial possibilities in Southeast Asia. Issue 2 (July 2022) - Gillen, Jamie; Bunnell, Tim; Rigg, Jonathan
The thoughtful and incisive responses to our article push us to address the central tension in our conceptualization of ruralization, which concerns how it both unsettles and reproduces binary thinking. On the one hand, we draw upon work in Southeast Asia that confounds binary mappings of urban versus rural space and associated divisions of labour in ways that redress the intellectual preponderance of the urban and urbanization. On the other hand, by proposing ruralization to do this, we arguably entrench a new variant of the binary (ruralization vs. urbanization). To address this tension, our response to the commentaries focuses on the ways in which they engage with the rural–urban binary. The conclusion briefly comments on the tricky pathways to theorize in step with the voices, practices, and imaginations of people in the Global South.